2016
DOI: 10.1186/s11671-016-1365-1
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Phase Composition of Cold Isostatically Pressed and Pressureless Sintered Silicon Nitride

Abstract: The microstructure and physical properties of new Y2O3 and Al2O3 oxide-doped silicon nitride ceramics fabricated by cold isostatic pressing and free sintering were investigated. The phase composition of produced material was also studied by X-ray diffraction at room and elevated temperature. The fabricated ceramics featured a microstructure of Si5AlON7 grains with a fine-grained α-Si3N4 with a small amount of Y2SiAlON5. Described ceramics is attractive for many high-temperature structural applications due to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…The results obtained are extremely satisfactory, when compared with those of literature-where the liquid phase sintering technique is adopted in the latter: as examples, Matovic Bocanegra-Bernal [29] obtained the density ranges from 86 to 100% after several sintering techniques, with temperatures between 1500 and 1825°C; Huang et al [30], using a pulsed electric current sintering, obtained full density at 1650°C [18].…”
Section: Characterization Of Hpht Sintered Samplessupporting
confidence: 52%
See 4 more Smart Citations
“…The results obtained are extremely satisfactory, when compared with those of literature-where the liquid phase sintering technique is adopted in the latter: as examples, Matovic Bocanegra-Bernal [29] obtained the density ranges from 86 to 100% after several sintering techniques, with temperatures between 1500 and 1825°C; Huang et al [30], using a pulsed electric current sintering, obtained full density at 1650°C [18].…”
Section: Characterization Of Hpht Sintered Samplessupporting
confidence: 52%
“…The results of fracture toughness indicate that the ceramics present high K IC between 8.5 and 10 MPa m 1/2 , even without the presence of intergranular phase, and motivate its use as a cutting tool. Tatli et al [18], when studying sintering-aided Si 3 N 4 , found fracture toughness ranging from 4.2 to 5.3 MPa m 1/2 . According to data reported by Tapasztó et al [33], the fracture toughness values vary between 2 and 5 MPa m 1/2 .…”
Section: Mechanical Propertiesmentioning
confidence: 99%
See 3 more Smart Citations